An exertion of enhance milk yield of native Pabna cattle through using different types of calcium salt of fatty acid - Yeasmin, D; Islam, N; Sarker, NR; Huda, N; Habib, A; Tabassum, F (SAARC Journal of Agriculture, 2018)
Keeping consideration on increasing quality milk production through addition of conventional fat, an experiment accords CRD design was conducted at Bangladesh Livestock Research Institute, Savar, Dhaka for a period of 30 days including 5 days of digestibility trial. Twenty lactating Pabna cattle of average 250.1 ± 13.64 kg (Bos indicus) of initial body weight with average milk yield of 2.88 ± 0.38 kg were selected and divided into four groups randomly having five cows in each. The imposed treatments were T0, T1, T2, and T3; in where To= German grass + Concentrate mixture without Ca salt of fatty acid + 2.5 % DCP, T1= German grass + Concentrate mixture + 2.5 % soybean based Ca salt of fatty acid, T2= German grass + Concentrate mixture + 2.5 % mustard based Ca salt of fatty acid and T3= German grass + Concentrate mixture + 2.5% palm-oil based Ca salt of fatty acid. The result showed that, calcium salt of fatty acid influenced to increase of milk yield significantly among (P<0.001) the treatments; in where highest yield gained in T1 (3.53 kg d-1) followed by T2, T0 and T3 (3.33, 2.44 and 2.24, respectively). Besides this, all other parameters analytically examined in this experiment i.e. intake, apparent digestibility, gained body weight and chemical composition of milk showed non-significant difference among the treatments. From the analytical value and discussion, it may be suggested that, calcium salt of fatty acid formulated from soybean oil or mustard oil could be used for enhancing better quality milk yield. SAARC J. Agri., 15(2): 137-146 (2017)